Adsorptive and capacitive properties of the activated carbons derived from pig manure residues. Issue 3 (June 2019) - Zhang, Xiaona; Mao, Xuhui; Pi, Liu; Wu, Tian; Hu, Yue
Abstract: Converting pig manure residues (PMR) into value-added activated carbon is a promising method to cope with the challenge of PMR disposal. In the present study, PMR were used as the precursors to prepare activated carbon (AC) materials. The performances of the AC materials prepared by chemical activation routes (with KOH and H3 PO4 ), and by the physical activation route (with CO2 gas) were accordingly compared. Elevated heavy metal Ni was detected in both the PMR and the prepared AC materials, but the Ni contents in all the samples still met the threshold values for agricultural use. The investigation of pore structure revealed that the KOH-activated carbon, which was prepared by the activation of PMR-derived biochar, had the maximum surface area (2335.9 m 2  g −1 ) and the largest micropore volume. H3 PO4 -activated carbon exhibited the most developed mesoporosity and the lowest surface area of 500.7 m 2  g −1 . Adsorption studies were conducted to evaluate the adsorption properties of the carbons toward methylene blue (MB). The obtained biochar did not show significant adsorptive performance for MB, whereas the activated carbons showed different performances. The adsorption of MB onto the activated carbons was well described by the pseudo-second order kinetic model and Langmuir isotherm. KOH-activated carbon exhibited the highest maximum monolayer adsorption capacity of 717.0 mg g −1, followed by H3 PO4 and CO2 -activated carbons. The adsorption property of KOH-activated carbon was apparently superior to that of three commercial activated carbons. In terms of the capacitive properties, KOH and CO2 -activated carbons showed excellent double-layer capacitance.